The Future Of Law From The Jurisprudence Perspective For Example: The Influence Of Science & Technology To Law, AI Law - Rehna Gul; Abdallah Mohamed Othman El Nofely (Fakultas Hukum, Universitas Warmadewa, 2021)
The field of law is as old as the human civilization. In the ancient Holy Scriptures the laws of humans, God made Laws, laws of nature, cultural laws, trade laws etc. have been discussed around the world. Even in the stone ages humans were following certain principles and laws which were the basis of law. The sense of right and wrong, truth and lie, positive and negative and so on is something engraved in the humans. Although there is another aspect that some humans consider the wrong as right and right as wrong. There have been different eras in which the scholars of law have made their valuable contributions in their respective societies and communities. The scholars of law are widely known as jurists of law and their contribution has evolved the philosophy of law which is called the Jurisprudence of law. The world in which we are living has laws which have basis from the contributions of renowned scholars of law from different cultures and parts of the world. This article touches the historical perspective, present scenario and future of law. Especially the use of technology in law has brought a revolutionary change in recent decades. The computers, cell phones, social media, internet as a whole, Google play store applications, laptops, i pods and various other devices have made significant changes in old practices and present day practices in the field of law. The judges, law teachers, professors, lawyers, litigants and all persons associated with them are taking immaculate advantage of technology in the field of law. The research methods and techniques have been made simple. This is a fast world in which we are living. No one has time for anything in this era. With the use of technology many time consuming activities can be performed in minutes and seconds in this era. We are heading in a direction of more human friendly and time saving environment. Although humans in different parts of the world have different cultures, norms, ethics, eating habits, religions, physical appearances and opinions but there are certain norms and international practices which are widely accepted around the world. Probably the future of law cannot be predicted at this moment of time because sometimes what the eyes see cannot be spoken rather it can only be seen with the passage of time.